TRANSFORMATION OF CONSULTING VALUABLE ORIENTATIONS OF MODERN UKRAINIAN STUDENT - Horban, Olexandr; Kuprii, Tetyana; Ovsiankina, Liudmyla (Educological discourse, 2019)
The article deals with the problem of the dynamics of the manifestation of value orientations of modern Ukrainian students, the patterns of their occurrence and factors influencing their formation in the context of philosophical, sociological, ethical and cultural dimensions and cross-cultural comparative studies. The article focuses on the problem of the existence of modern youth, the formation of new ideological and humanistic values, and the search for basic principles of world attitude in the conditions of transformational changes in society as a whole. The process of integrative and social development of modern youth, which is accompanied the changes of hierarchical correlations of values and appearance of new, and also socially psychological features which show up on the different levels of valued-normative sphere of personality in a socio-cultural context under act of gender-age factors, is analysed. It is rotined that principles of organization, logician of functioning and processes which generate the individual and superindividual systems of values at all of likeness of common concepts have different nature and require different interpretations accordingly. Development of method of practical research of the individual and / either superindividual systems of values requires the constructions of operational determination of key categories which are utillized in research. From the functional point of view instrumental values activate as criteria, as standards of estimation during a choice only to modus (to the method) of conduct or actions, and a terminal is utillized an individual during the estimation of both aims of activity and possible methods of their achievement.